PENGUKURAN DAN SIMULASI PENGURANGAN HARMONISA DENGAN FILTER PASIF PADA SISTEM PLTS - Agung Budi Muljono; I Made Ginarsa (DIELEKTRIKA, 2019)
Power quality consists of several variables such as voltage, current, frequency, power factor, and harmonics. All of these variables must have good quality when operating so that electricity reaches consumers. Indonesia is a country that has two seasons namely the rainy season and the dry season so that the suitable renewable generating system is the photovoltaic system. The National Energy Council (DEN) has introduced, in 2025 the utilization of EBT is expected to increase from 5.7% to 23% in 2025. The photovoltaic system has an energy conversion process using an inverter which is a non-linear device that can generate harmonics which are usually denoted by Total Harmonic Distortion (THD). If harmonics continue to occur, the performance of the equipment or load will not have good performance when operating. In this research, measurements and simulations of harmonic reduction with a passive filter were taken, namely single tune filter on the photovoltaic On-Grid system. Measurements were made using a power quality measuring device namely 3 Phase Power and Harmonic Analyzer. The measurement results obtained by the value of THDi of 33.33% using linear and non-linear combined loads. After the measurement, a filter simulation was designed to reduce harmonics on order 3, 5, 7, 9, and 11. Simulation results after filter installation, harmonics which can be reduced by 20.55% in order 3 with parameters L = 0.200 mH and C = 2.95 uF . Based on the IEEE standard 512-1992 the harmonic value is in accordance with the permitted standard of 20%.